Investigation on classification of natural wetlands in Zhejiang province - CHEN Zheng-hai; LIU An-xing; LI Geng-you; DU Qun; YING Shun-dong (浙江大学学报. 农业与生命科学版, 2002)
In accordance with classification of wetlands by Lamsar Convention and the features of natural wetlands in Zhejiang, a classification system for natural wetlands in Zhejiang is submitted for the first time in which natural wetlands in Zhejiang are divided into 4 groups, 16 types, and the distribution of each type is described too. According to an investigation, the wetland types of Zhejiang are diversified and the gross area of main wetlands with size over 100 hm2 amounts to (68.8×104) hm2. The main wetlands in Zhejiang distribute mostly on the plains and coastal regions. The coastal wetlands is the most important with respect to their total area and extensive distribution in Zhejiang.